Understanding the microbiome–crop rotation nexus in karst agricultural systems: insights from Southwestern China - Wang, Bin; Shang, Nianjie; Feng, Xinwei; Hu, Zongling; Li, Pengfei; Chen, Yi; Hu, Binbin; Ding, Mengjiao; Xu, Junju (Frontiers in Microbiology, 2025)
Understanding how soil properties and microbial communities respond to crop rotation is essential for the sustainability of agroecosystems. However, there has been limited research on how crop rotation alters below-ground microbial communities in soils with serious bacterial wilt within the karst agricultural system. This study investigated the effects of continuous planting of corn, tobacco, and tobacco–corn rotation on soil microbial communities in the karst regions of Southwestern China. High-throughput sequencing was used to evaluate the responses of the soil microbial community structure to crop monoculture and rotation patterns. As expected, the tobacco–corn rotation mitigated the negative effects of continuous cropping and reduced soil acidification. The tobacco–corn rotation also significantly altered the composition of microbial communities and promoted plant growth by fostering a higher abundance of beneficial microorganisms. The predominant bacteria genera Sphingomonas and Gaiella and the predominant fungal genera Mortierella and Saitozyma were identified as discriminant biomarkers that are critical to soil ecosystem health. pH, available potassium (AK), and available phosphorus (AP) were the primary soil factors related to the soil microbiome assembly. This study aimed to demonstrate the association between crop rotation and microbiomes, suggesting that altering cultivation patterns could enhance karst agricultural systems.